2019
DOI: 10.1111/aas.13316
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in the critically ill: A prospective observational study of occurrence, risk factors and outcome

Abstract: Background:The aim of the study was to explore occurrence, risk factors and outcome of venous thromboembolism (VTE) in intensive care unit (ICU) patients. Methods: Prospective observational study of ICU patients receiving thromboprophylaxis at Oslo University Hospital in Norway. Adult medical and surgical patients with ICU length of stay (LOS) longer than 48 hours were included. For detection of VTE, Doppler ultrasound screening of neck, upper and lower extremity veins was used, and computed tomography angiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 42 publications
0
23
3
Order By: Relevance
“…More importantly, whereas a prior study evaluating non-COVID-19 ICU patients found that patients with and without VTE had comparable mortality risk (16% vs 20%, P = 0.72) [66] , our meta-analysis shows that concomitant TE and COVID-19 is associated with 74% increased odds of death compared to COVID-19 patients without TE (13% vs 23%, OR: 1.74, P = 0.04). The risk of death in COVID-19 posed by TE is therefore not negligible.…”
Section: Discussioncontrasting
confidence: 81%
“…More importantly, whereas a prior study evaluating non-COVID-19 ICU patients found that patients with and without VTE had comparable mortality risk (16% vs 20%, P = 0.72) [66] , our meta-analysis shows that concomitant TE and COVID-19 is associated with 74% increased odds of death compared to COVID-19 patients without TE (13% vs 23%, OR: 1.74, P = 0.04). The risk of death in COVID-19 posed by TE is therefore not negligible.…”
Section: Discussioncontrasting
confidence: 81%
“…This is significantly higher than described for non-COVID-related critical illness where there is a VTE prevalence between 5 and 30%. 3,4,[19][20][21][22][23][24][25][26] The direct comparison of studies describing the incidence of VTE is limited by the various thromboprophylactic regimes used, by differences in patient populations and by the differing imaging modalities used to establish a diagnosis of VTE. A few studies have compared patients with COVID-19 to historical cohorts of patients with acute respiratory distress syndrome (ARDS) or to critically ill patients with bacterial or viral pneumonia.…”
Section: Prevalence Of Vte In Patients With Covid-19mentioning
confidence: 99%
“…Patients included in the NORIDES study received standard treatment with additional Doppler ultrasound screening of veins to detect venous thromboembolism (VTE), and additional blood samples drawn from intravascular catheters for coagulation analyses. The main results of the NORIDES study describing the occurrence, risk factors and outcome of VTE is published [29], and additional results of coagulation tests are pending. In the NORIDES study, informed consent for participation was obtained from the patients or their next of kin in cases when patients were incompetent to give consent.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…Data from all patients considered for inclusion in the NORIDES study were included in this study; a detailed description of the study population is provided elsewhere [29].…”
Section: Study Populationmentioning
confidence: 99%